2010
DOI: 10.1177/1557988310370360
|View full text |Cite
|
Sign up to set email alerts
|

Aging Men and Lipids

Abstract: Many theories aim at explaining the mechanisms of aging and death in humans. Decreased levels of androgens, growth hormone, and insulin-like growth factor accompany natural aging in men. Androgens influence the growth and maturation of men in various stages of their life. The action of androgens is performed by binding or not binding to androgen receptors. However, various actions of androgens were clarified after the discovery and genotyping of the androgen receptor. The influence of androgens on the lipid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 163 publications
(194 reference statements)
1
18
1
3
Order By: Relevance
“…The mTOR pathway is highly conserved and regulates processes including protein synthesis, lipid metabolism, glycolysis, angiogenesis, apoptosis, inflammation and autophagy (Proud, 2011) (Figure 1). Increasing age has been associated with perturbations to most of these factors; decreases in protein synthesis with age are well documented in various tissues in man and animal models (Kennedy and Kaeberlein, 2009), whereas age-related increases to lipid profiles (AbouRjaili et al, 2010; Kolovou et al, 2011) and inflammatory processes (Chung et al, 2011) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR pathway is highly conserved and regulates processes including protein synthesis, lipid metabolism, glycolysis, angiogenesis, apoptosis, inflammation and autophagy (Proud, 2011) (Figure 1). Increasing age has been associated with perturbations to most of these factors; decreases in protein synthesis with age are well documented in various tissues in man and animal models (Kennedy and Kaeberlein, 2009), whereas age-related increases to lipid profiles (AbouRjaili et al, 2010; Kolovou et al, 2011) and inflammatory processes (Chung et al, 2011) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The results stated to the well-adjusted reliability and validity of MASSQ and usefulness of it in the relevant studies as well. Therefore, future researchers should not limit themselves to the western scales[720] but should also consider specific cultural factors. Additionally, it is suggested that in future studies, the female menopause symptoms self-assessment questionnaire, which are compatible with Iran's native culture, be conducted and evaluated as well.…”
Section: Discussionmentioning
confidence: 99%
“…The MASSQ questionnaire mainly consists of a 25-item disability/symptom scale regarding andropause that was investigated by authors and literature reviews. [24712192123262834] Each item in the disability/symptom scale has five response options from 1 = none to 5 = extremely severe. If the 25 items are completed, a scale score ranging from 25 (no symptoms) to 125 (most severe symptoms) can be calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…94 nonostante siano ancora poco chiari i meccanismi sui quali gli ω3 intervengono, autorità sanitarie in vari paesi hanno recentemente raccomandato la produzione di alimenti, in particolare uova, yogurt, latte, arricchiti con tali acidi grassi per aumentarne l'assunzione. 93,95 Attualmente l'American heart Association ha definito auspicabile l'assunzione di acidi grassi ω3 con almeno due porzioni alla settimana di pesce e utilizzando oli vegetali ricchi di acido α-linolenico (canola, soia, ecc.). Per i pazienti con documentato rischio cardiovascolare, suggerisce, inoltre, un apporto di circa 1 g al giorno di ePA e dhA, provenienti da pesci grassi o da integratori alimentari.…”
Section: Intolleranze E Allergieunclassified